Equações preditivas para as pressões respiratórias estáticas máximas de adolescentes brasileiros - Mendes, Raquel Emanuele de França (2012)
Introduction: The reference values and prediction equations for maximal respiratory pressures (MRP) differ significantly between the available studies. This large discrepancy can be attributed to the different methodologies proposed. Although the importance of MRP is widely recognized, there are no Brazilian studies that provide predictive equations and reference values for PRM adolescents. Objectives: The purpose of this study was to provide normal values and propose predictive equations for maximal static respiratory pressures of Brazilian adolescents. Methods: An observational cross-sectional study, which evaluated 182 adolescents of both sexes aged between 12 and 18 years, enrolled in schools of the state and private in the city of Natal / RN. The selection of schools and participants of the study was randomly through a lottery system. The spirometric evaluation was performed through the digital spirometer One Flow FVC prior to the assessment of respiratory muscle strength. The MICs were measured with MVD digital manometer 300. Statistical analysis was performed using the SPSS 17.0 software STATISTICS, assigning the significance level of 5%. The normality of data distribution was verified using the Kolmogorov-Smirnov (KS). The descriptive analysis was expressed as mean and standard deviation. We used one-way ANOVA test to verify the difference of the averages of MRPs between age and gender and comparing the averages of MRPs between levels of physical activity. The test t'Student unpaired compared the averages of MRPs being ages and sexes. The comparison of mean values obtained in this study PRM with the values predicted using the equations mentioned above was relizada by testing paired t'Student. To verify the correlation between the PRM and the independent variables (age, weight, height) was used Pearson correlation test. Levene's test evaluated the homogeneity of variance. To obtain predictive equations analysis was used stepwise multiple linear regression. Results: There was no significant difference in mean age between the PRM. The male adolescents, regardless of age, showed superiority in MRP values when compared to the opposite sex. Weight, height and sex correlated with the PRM. Regression analysis suggested in this study, pointed out that the weight and sex had an influence in MIP and MEP only in relation to sex influenced. The mean for each PRM adolescents classified as very active were superior to those observed in adolescents classified as irregularly active. Conclusion: This study provides reference values and two models of predictive equations for maximal inspiratory and expiratory pressures, and to establish the lower limits of normality that will serve as an indispensable condition for careful evaluation of respiratory muscle strength in Brazilian adolescents